Gender games. Gender roles in sport social media challenges: a content analysis - Azzarita, Vittoria; Carbonari, Maddalena; Grasso, Marta; Miraglia, Cosimo (Ámbitos. Revista Internacional de Comunicación, 2023)
This research investigates the sport practice through the lens of gender on digital platforms. Since they are involved in the construction of corporeality, sports tend to reproduce socially dominant values about what being a woman, or a man means. Consequently, the idea that there are «feminine sports» and «masculine sports» is widespread. Specifically, sporting practices through the phenomenon of social media challenges are focused. These are highly correlated with concepts such as challenge and performance, in which gender, too, is enacted. The aim is to explore to what extent these sport challenges promote predominant ideas about femininity and masculinity, and in what cases they question them. To achieve these objectives, we used a dataset of about one thousand videos, shared on four social networking platforms during the period between 1 January 2020 and 31 January 2021. From this dataset, 136 social media challenges marked for «sport,» «physical ability,» or «fitness» were selected. Content analysis, chosen as the method of analysis, shows how through these new challenges traditional gender differences are perpetuated and promoted rather than challenged. In this regard, although digital platforms have created new symbolic and expressive spaces in which once unthinkable forms of self-representation and interaction can be implemented and new possibilities of agency are developed, sport social media challenges do not yet appear to be fully involved in that process.